Geochemistry of serpentinized and multiphase altered Atlantis Massif peridotites (IODP Expedition 357): Petrogenesis and discrimination of melt-rock vs. fluid-rock processes - Whattam, Scott A.; Frueh-Green, Gretchen L.; Cannat, Mathilde; De Hoog, Jan C. M.; Schwarzenbach, Esther M.; Escartin, Javier; John, Barbara E.; Leybourne, Mathew; Williams, Morgan J.; Roumejon, Stephane; Akizawa, Norikatsu; Boschi, Chiara; et al. (Chemical Geology, 2022)
International Ocean Discovery Program (IODP) Expedition 357 drilled 17 shallow sites distributed similar to 10 km in the spreading direction (from west to east) across the Atlantis Massif oceanic core complex (Mid-Atlantic Ridge, 30 degrees N). Mantle exposed in the footwall of the Atlantis Massif oceanic core complex is predominantly nearly wholly serpentinized harzburgite with subordinate dunite. Altered peridotites are subdivided into three types: (I) serpentinites, (II) melt-impregnated serpentinites, and (III) metasomatic serpentinites. Type I serpentinites show no evidence of melt-impregnation or metasomatism apart from serpentinization and local oxidation. Type II serpentinites have been intruded by gabbroic melts and are distinguishable in some cases on the basis of macroscopic and microscopic observations, e.g., mm-cm scale mafic-melt veinlets, rare plagioclase (<0.5 modal % in one sample) or by the local presence of secondary (replacive) olivine after orthopyroxene; in other cases, 'cryptic' melt-impregnation is inferred on the basis of incompatible element enrichments. Type III serpentinites are characterized by silica metasomatism manifest by alteration of orthopyroxene to talc and amphibole, and by anomalously high anhydrous SiO2 concentrations (59-61 wt%) and low MgO/SiO2 values (0.48-0.52). Although many chondrite-normalized rare earth element (REE) and primitive mantle-normalized incompatible trace element anomalies, e.g., negative Ce-anomalies, are attributable to serpentinization, other compositional heterogeneities are due to melt-impregnation. On the basis of whole rock incompatible trace elements, a dominant mechanism of melt-impregnation is distinguished in the central and eastern serpentinites from fluid-rock alteration (mostly serpentinization) in the western serpentinites, with increasing melt-impregnation manifest as a west to east increase in enrichment in high-field strength elements and light REE. High degrees of melt extraction are evident in low whole-rock Al2O3/SiO2 values and low concentrations of Al2O3, CaO and incompatible elements. Estimates of the degree of melt extraction based on whole rock REE patterns suggest a maximum of similar to 20% non-modal fractional melting, with little variation between sites. As some serpentinite samples are ex situ rubble, the magmatic histories observed at each site are consistent with a local source (from the fault zone) rather than rafted rubble that would be expected to show more heterogeneity and no spatial pattern. In this case, the studied sites may provide a record of enhanced melt-rock interactions with time, consistent with proposed geological models. Alternatively, sites may signify heterogeneities in these processes at spatial scales of a few km.
CRIS-Team WoS Importer:2022-04-08

Water contents of nominally anhydrous orthopyroxenes from oceanic peridotites determined by SIMS and FTIR - Wenzel, Kirsten; Wiedenbeck, Michael; Gose, Jürgen; Rocholl, Alexander; Schmädicke, Esther (Mineralogy and Petrology, 2021)
This study presents new secondary ion mass spectrometry (SIMS) reference materials (RMs) for measuring water contents in nominally anhydrous orthopyroxenes from upper mantle peridotites. The enstatitic reference orthopyroxenes from spinel peridotite xenoliths have Mg#s between 0.83 and 0.86, Al2O3 ranges between 4.02 and 5.56 wt%, and Cr2O3 ranges between 0.21 and 0.69 wt%. Based on Fourier-transform infrared spectroscopy (FTIR) characterizations, the water contents of the eleven reference orthopyroxenes vary from dry to 249 +/- 6 mu g/g H2O. Using these reference grains, a set of orthopyroxene samples obtained from variably altered abyssal spinel peridotites from the Atlantic and Arctic Ridges as well as from the Izu-Bonin-Mariana forearc region was analyzed by SIMS and FTIR regarding their incorporation of water. The major element composition of the sample orthopyroxenes is typical of spinel peridotites from the upper mantle, characterized by Mg#s between 0.90 and 0.92, Al2O3 between 1.66 and 5.34 wt%, and Cr2O3 between 0.62 and 0.96 wt%. Water contents as measured by SIMS range from 68 +/- 7 to 261 +/- 11 mu g/g H2O and correlate well with Al2O3 contents (r = 0.80) and Cr#s (r(.) = -0.89). We also describe in detail an optimized strategy, employing both SIMS and FTIR, for quantifying structural water in highly altered samples such as abyssal peridotite. This approach first analyzes individual oriented grains by polarized FTIR, which provides an overview of alteration. Subsequently, the same grain along with others of the same sample is measured using SIMS, thereby gaining information about homogeneity at the hand sample scale, which is key for understanding the geological history of these rocks.
CRIS-Team WoS Importer:2021-09-10

Water in orthopyroxene from abyssal spinel peridotites of the East Pacific Rise (ODP Leg 147: Hess Deep) - Hesse, Kirsten; Gose, Jürgen; Stalder, Roland; Schmädicke, Esther (Lithos, 2015)
Keywords: Geothermometry; East Pacific Rise; Nominally anhydrous minerals; Infrared spectroscopy; Upper mantle; Orthopyroxene water content